2020
DOI: 10.3390/math8050784
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady Three-Dimensional MHD Non-Axisymmetric Homann Stagnation Point Flow of a Hybrid Nanofluid with Stability Analysis

Abstract: The hybrid nanofluid under the influence of magnetohydrodynamics (MHD) is a new interest in the industrial sector due to its applications, such as in solar water heating and scraped surface heat exchangers. Thus, the present study accentuates the analysis of an unsteady three-dimensional MHD non-axisymmetric Homann stagnation point flow of a hybrid Al2O3-Cu/H2O nanofluid with stability analysis. By employing suitable similarity transformations, the governing mathematical model in the form of the partial differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

6
4

Authors

Journals

citations
Cited by 59 publications
(27 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…Moreover, dual solutions of hybrid nanofluid flow were examined by Waini et al [34][35][36][37][38][39]. Other physical aspects have been considered by several authors [40][41][42][43][44][45][46][47][48][49] and review papers are also available [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, dual solutions of hybrid nanofluid flow were examined by Waini et al [34][35][36][37][38][39]. Other physical aspects have been considered by several authors [40][41][42][43][44][45][46][47][48][49] and review papers are also available [50][51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Bachok et al [6] concluded that inclusion of the unsteadiness parameter offers a significant impact towards the boundary layer flow in nanofluid and Fan et al [7] presented analytical solutions using the homotopy analysis method (HAM) and managed to advertise a highly precise analytical estimation which is in excellent agreement with the numerical results offered by the Keller box scheme. It is worth mentioning that a considerable amount of reviews on the unsteady stagnation point flow due to a stretching/shrinking surface have been accomplished by numerous researchers, including [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Suresh et al 22 , 23 led the exploratory effort utilizing to examine the upgrade of the liquid thermal conductivity. Afterwards numerous investigators carried various studies for hybrid nanofluid by considering stretching/shrinking surfaces such as Waini et al 24 , 25 , Zainal et al 26 and Khashi’ie et al 27 , 28 . Relationships of thermal conductivity for ordinary nanofluids are completely examined and this study emphasizes planning, complications and challenges of hybrid nanofluids by Das 29 .…”
Section: Introductionmentioning
confidence: 99%